PENGARUH KUALITAS KONTEN DAN FREKUENSI POSTINGAN TERHADAP LOYALITAS PENGIKUT PADA KONTEN KREATOR TIKTOK (STUDI KASUS PADA MAHASISWA FEB UNIVERSITAS PANCASAKTI BEKASI) - Amelia Alvina Dewi; Sugeng Prayetno; Moh. Taufan Nugroho (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to analyze the influence of content quality and posting frequency on follower loyalty among TikTok content creators, focusing on students of the Faculty of Economics and Business at Pancasakti University Bekasi. As a short video-based social media platform, TikTok has a significant impact on audience engagement, making content strategy a crucial factor in building follower loyalty. This research employs a quantitative approach, with data collected through questionnaires distributed to 90 respondents. Data analysis was conducted using multiple linear regression. The results indicate that both content quality and posting frequency have a positive and significant influence on follower loyalty. Posting frequency has a greater impact compared to content quality, with a coefficient of determination value of 61.7%. These findings emphasize that TikTok creators need to pay attention to both the quality and consistency of their content uploads. Both factors have proven effective in building engagement, interaction, and loyalty among followers, particularly among young users such as university students.